ESTUDO QUANTITATIVO DE CARACTERÃSTICAS ANATÃ”MICAS DA FOLHA DE Panicum maximum JACQ. E Panicum coloratum L. - Rodella, Roberto AntÃ´nio; Ayoub, Jorge Fehed; Rodella, Rita C. S. Maimoni (REVISTA DE AGRICULTURA, 2015)
ESTUDO QUANTITATIVO DE CARACTERÃSTICAS ANATÃ”MICAS DA FOLHA DE Panicum maximum JACQ. E Panicum coloratum L.